Assessment of recurrence and complications following uncomplicated diverticulitis. Issue 7 (17th April 2013) - Buchs, N. C.; Konrad‐Mugnier, B.; Jannot, A.‐S.; Poletti, P.‐A.; Ambrosetti, P.; Gervaz, P.
<x xml:space="preserve">Abstract</x> Background The natural history of sigmoid diverticulitis has been inferred from population‐based or retrospective studies. This study assessed the risk of a recurrent attack following the first episode of uncomplicated diverticulitis. Methods Patients admitted between January 2007 and December 2011 with a first episode of uncomplicated sigmoid diverticulitis confirmed on computed tomography were enrolled in this prospective study. After successful medical management of the first episode, follow‐up was conducted through yearly telephone interviews. Cox proportional hazards regression was performed to model the impact of various parameters on eventual recurrences and complications. Results During a median follow‐up of 24 (range 3–63) months, 46 (16·4 per cent) of 280 patients experienced a second episode of diverticulitis. Six patients (2·1 per cent) subsequently developed complicated diverticulitis and four (1·4 per cent) underwent emergency surgery for peritonitis. In multivariable analysis, a raised serum level of C‐reactive protein (over 240 mg/l) during the first attack was associated with early recurrence (hazard ratio 1·75, 95 per cent confidence interval 1·04 to 2·94; P = 0·035). Conclusion Uncomplicated sigmoid diverticulitis follows a benign course with few recurrences and little need for emergency surgery. Registration number: NCT01015378 (http://www.clinicaltrials.gov).